Nasalance Changes Following Various Endonasal Surgeries - Amer, Hazem Saeed; Elaassar, Ahmed Shaker; Anany, Ahmad Mohammad; Quriba, Amal Saeed (International Archives of Otorhinolaryngology, 2017)
Introduction There is change in nasalance post endonasal surgery which is not permanent.Objectives The objective of this study is to evaluate the long-term nasalance changes following different types of endonasal surgeries.Methods We included in this study patients who underwent sinonasal surgery at the Otorhinolaryngology Department in Zagazig University Hospitals from February 2015 until March 2016. We divided the patients into two groups according to the surgeries they underwent: Group (A) was the FESS group and group (B), the septoturbinoplasty group. We checked nasalance using a nasometer before and after the sinonasal surgery.Results Nasalance increased at one month after the operation in both groups. However, it returned to nearly original levels within three months postoperatively.Conclusion FESS, septoplasty, and turbinate surgery may lead to hypernasal speech. This hypernasal speech can be a result of change in the shape and diameter of the resonating vocal tract. Hypernasal speech in these circumstances may be a temporary finding that can decrease with time. Surgeons should inform their patients about the possibility of hypernasality after such types of surgery, especially if they are professional voice users.
Keywords: speech; turbinate; endoscopy; sinusitis